Externalities and common pool licenses: An experimental study of managing differing natural resource uses - Thomas J. Frye (Agricultural and Resource Economics Review)
In this paper, I discuss dual collective action problems in which a resource pool has simultaneous common pool and public good aspects in its usage, such as hunting (consumption) and conservation of wildlife. I then implement laboratory experiments to evaluate how spillovers between the two related uses of nature affect the consumption and conservation habits of stakeholders. The Nash predictions suggest that even the most selfish of profit-maximizing agents have an incentive to provide equally towards resource consumption and conservation when resource spillovers are present. Results from laboratory experiments are consistent with this hypothesis. As a policy intervention, I introduced and later revoked a common pool licensing policy based on U.S. hunting and fishing licensing. Under the same theoretical framework, removing a common pool licensing policy would increase welfare for all resource stakeholders. Contrary to this, experimental evidence indicates no overall change in welfare.